1985
DOI: 10.1007/bf00391888
|View full text |Cite
|
Sign up to set email alerts
|

Fecal skatole and indole and breath methane and hydrogen in patients with large bowel polyps or cancer

Abstract: The object of this study was to explore the use of fecal skatole and indole and breath methane and hydrogen as metabolic markers of the anaerobic colonic flora in patients with unresected large bowel cancer or polyps. Patients with descending or sigmoid colon cancer were more likely to be breath methane excretors than control subjects, patients with proximal colon cancer, and patients with rectal cancer. Control subjects excreting breath methane excreted less fecal skatole than breath methane excretors in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 21 publications
2
81
1
Order By: Relevance
“…The stool samples we used had been stored at Ϫ80°C for 10 to 20 years, and to our knowledge, there is no published literature regarding indole stability under such conditions. However, our stage 1 indole levels were consistent with values from control individuals in two earlier studies using freshly collected stool samples (43,44), although direct comparisons could not be made since stool samples were prepared, extracted, and tested by different techniques. Further, all of the stool samples we used were stored under the same conditions and the indole concentrations in samples from 1993 to 1998 were no different from those in samples from 1999 to 2004.…”
Section: Discussionsupporting
confidence: 50%
“…The stool samples we used had been stored at Ϫ80°C for 10 to 20 years, and to our knowledge, there is no published literature regarding indole stability under such conditions. However, our stage 1 indole levels were consistent with values from control individuals in two earlier studies using freshly collected stool samples (43,44), although direct comparisons could not be made since stool samples were prepared, extracted, and tested by different techniques. Further, all of the stool samples we used were stored under the same conditions and the indole concentrations in samples from 1993 to 1998 were no different from those in samples from 1999 to 2004.…”
Section: Discussionsupporting
confidence: 50%
“…Few studies have reported indole concentrations in the stools of healthy adults. Gas chromatographic analysis of indole and 3-methylindole (skatole) from the fecal samples of 84 patients with colorectal cancers, 20 postsurgical cholecystectomy patients, and 15 healthy control patients reported concentrations in the 5-to 156-g/g range for the two molecules (29,30). These values are roughly consistent with what we found but cannot be compared directly since the data were expressed per gram (dry weight) of feces.…”
Section: Discussionsupporting
confidence: 81%
“…However, we did find that high concentrations of indole inhibit the detection of AHL by SdiA. We see a gradation of inhibition between 100 M and 1 mM indole, which may be physiologically relevant since indole is reported to be present in the mouse, rat, and human gut at ϳ140 M, ϳ68 M, and ϳ300 to 1,074 M concentrations, respectively (3,15,31,38).…”
mentioning
confidence: 72%